A one-step reverse-transcription recombinase aided PCR assay for the rapid and sensitive detection of human enteroviruses - Xiuli Sun; Huanhuan Lu; Yanqing Tie; Mengchuan Zhao; Ruiqing Zhang; Zhenlu Sun; Guohao Fan; Fengyu Li; Fengyu Tian; Yaxin Hu; Mengyi Zhang; Xinxin Shen; et al. (Elsevier, 2023)
Human enteroviruses (HEVs) include many different types that cause a wide range of diseases, and an effective method of genus-level identification has therefore significant clinical implications. However, quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR), the gold-standard method, still has shortfalls in diagnostic sensitivity and timeliness. Here we established a one-step real-time reverse-transcription recombinase-aided PCR assay (RT-RAP) to detect HEV fragment within an hour. The RT-RAP assay showed a detection limit of 5 copies/μL using recombinant plasmids and was extensively verified using 15 HEV strains. Among 15 types of HEV (species A-C), the sensitivity of RT-RAP was approximately 2-8 folds lower than that of the qRT-PCR in 9 types, and no-cross reaction with other viruses was observed. RT-RAP was further applied to analyze CSF and fecal specimens; the clinical performance demonstrated that the RT-RAP and the commercial qRT-PCR kit provided consistent results. These results indicated that RT-RAP assay may be a promising approach for rapid and sensitive detection of HEV.